The Vowels of Nubri from the Perspective of Other Tibetan Languages - Donohue, Cathryn; Donohue, Mark (Nepalese Linguistics, 2023)
This paper presents the first illustration of the vowel system of the Samagaun dialect of Nubri. We present acoustic data for the nine oral vowels and illustrate the contrastive nasalisation that may be added to three of these vowels. We provide examples of length and non-modal phonation (breathiness and creak), also found in Nubri, but assume that these are a function of tonal contrasts, and not orthogonal to the differences in pitch. We then position the Nubri vowel system in the context of a range of Tibetan languages and discuss challenges for classifying Nubri as Tibetic in the context of possible developments and etymologies of some key words.